Measuring Islamic Bank's Performance Using CAMELS And RGEC Method Based On Indonesian Financial Services Authority Circular - Agung Abdullah (Journal of Business and Management Review, 2020)
This paper aims to determine the differences bank performance of Muamalat BankBank Sinarmas Bank, and BPRS Bhakti Sumekar measured by CAMELS (Capital, Asset, Management, Earning, Liquidity, Sensitivity to Market Risk) method and the RGEC (Risk profile, Good governance, Earning, Capital) method in 2018. The authors used quantitative methods with a descriptive approach. The sample taken in this study is a representation of Islamic commercial banks (Bank Muamalat), Islamic business unit banks (Bank Sinarmas Syariah), and Islamic microfinance banks (BPRS Bhakti Sumekar). The data used in this study are secondary data from the company's published financial report website and annual report. The Analysis techniques used are : 1) Bank Performance analysis using the CAMELS and RGEC methods. 2) Describe the differences in the measurement using the CAMELS and RGEC methods. Finding in this study is the RGEC is a more comprehensive method to measure Islamic bank performance than Camel. This study has limitation, the period used in this study is only 1 (one) year, for more valid results it is necessary to add the sample over several years.